Song, W.L., Lin, D., Li, M., Du, Q. & Chen, S.L. (2022) Four new records of myxomycetes from China. Phytotaxa 567 (2): 181–188. - Song, Wen-Long; Lin, Di; Li, Min; Du, Que; Chen, Shuang-Lin (Phytotaxa, 2022)
N/A